Effect of Arbuscularmycorrhizal Fungi and Poultry Manure on Growth and Nutrients Uptake by Maize under Field Condition - Rakiya, Abdullahi; Samuel, Lihan; Rebicca, E. (IJAIR, 2015)
Field experiment was conducted to study the effect of arbuscularmycorrhizal fungi (AMF) and poultry manure (PM) on the growth and nutrients uptake by maize. The experiment was laid out in a randomized complete block design with 6 levels of PM in tones ha-1 (0, 4, 6, 8, 10, & 12) and 2 levels of AMF; (inoculated , +AMF and un-inoculated, -AMF) + recommended dose of NPK (RD NPK) chemical fertilizer; making 13 treatment combinations replicated 3 times. Plant growth (height, leaf area, root volume, shoot, and root dry weight biomass), root colonization (RC %) and uptakes of N, P, & K were assessed after six weeks growing period of maize. Inoculated plants and RD NPK recorded higher values for plant growth biometrics and nutrients uptake compared to un-inoculated plants.Poultry manure application enhanced RC % and AMF spore density with maximum value (43.00±38.70 %, 17.33±1.202 g-1 soil) at 12 t PM ha-1. Applying 12 t PM+AMF produced plants with the highest shoot and root biomass weights (199.00±3.055, 9.57±0.713 g) that were comparable to RD NPK (194.33±2.404, 9.27±0.376 g). Increase in shoot dry biomass due to AMF revealed, 19.3%, 20%, 12.2%, 7.2%, 7.9%, and 15.2% over 0, 4, 6, 8, 10 & 12 t PM ha-1 of un-inoculated plants. Applying 12 t PM+AMF recorded higher shoot dry biomass by 2.3% over RD NPK. RC % correlated positively with shoot biomass (R2= 0.753). Maximum N, P, & K uptake were recorded at 12 t PM+AMF compared to all the treatments. It could be concluded that PM have potentially stimulated AMF symbiosis, enhanced maize growth and nutrients uptake under normal field condition compared to chemical fertilizer, thus could be considered for maize production.